Are welders more at risk of respiratory infections? Findings from a cross-sectional survey and analysis of medical records in shipyard workers: the WELSHIP project. Issue 7 (30th March 2016) - Marongiu, Andrea; Hasan, Omar; Ali, Anila; Bakhsh, Sharoon; George, Bobby; Irfan, Nabeel; Minelli, Cosetta; Canova, Cristina; Schofield, Susie; De Matteis, Sara; Cullinan, Paul
Abstract : Background: Exposure to welding fume increases the risk of pneumococcal infection; whether such susceptibility extends to other respiratory infections is unclear. We report findings from a survey and from medical consultation data for workers in a large shipyard in the Middle East. Methods: Between January 2013 and December 2013, we collected cross-sectional information from 529 male workers variously exposed to welding fume. Adjusted ORs for respiratory symptoms (cough, phlegm, wheezing, shortness of breath and 'chest illness') were estimated using multivariable logistic regression. Subsequently, we examined consultation records from 2000 to 2011 for 15 954 workers who had 103 840 consultations for respiratory infections; the associations between respiratory infections and levels of welding exposure were estimated using a count regression model with a negative binomial distribution. Results: 13% of surveyed workers reported respiratory symptoms with a higher prevalence in winter, particularly among welders. The adjusted OR in welders versus other manual labourers was 1.72 (95% CI 1.02 to 3.01) overall and 2.31 (1.05 to 5.10) in winter months; no effect was observed in summer. The risk of consultation for respiratory infections was higher in welders than in manual labourers, with an adjusted incidence rate ratio of 1.45 (1.59 to 1.83) overall, 1.47 (1.42 to 1.52) in winter and 1.33 (1.23 to 1.44) in summer (interaction, p<0.001). Conclusions: The observation that respiratory symptoms and consultations for respiratory infection in welders are more common in winter may indicate an enhanced vulnerability to a broad range of infections. If confirmed, this would have important implications for the occupational healthcare of a very large, global workforce.